Cross-border class actions: the European way - Nuyts, Arnaud (Sellier european law publishers, 2013)
Whether with regard to mass torts or as means of private enforcement of antitrust policies: Collective redress of civil claims has been gaining in importance in Europe and worldwide. In the last years, some EU Member States have made their own attempts at collective redress institutions. In this book, distinguished experts evaluate the problems of cross-border class actions and make proposals for a "European way" appropriate for the 21st century.